An equation has roots 1 - i and 1 + i. What is the equation?

3 Answers | Add Yours

atsuzuki's profile pic

atsuzuki | (Level 1) Adjunct Educator

Posted on

To solve questions of this type and remember it, the easiest way is to start by writing the statement of the question in math form, that is,

x = 1-i

and 

x = 1+i 

are two of the roots of the "unknown" equation. Then from them we rewrite each as a solution of the simplest connected equation possible, that is, write everything on the left side of the equal sign and the right side with of course zero, because it is a root of the equation:

From the first,

`x=1-irArr x-(1-i) = 0`

``From the second,

`x=1+irArr x-(1+i) =0`

Since we want both roots to belong to the same equation, just multiply the two and make them equal to zero:

`[x-(1-i)]*[x-(1+i)]=0`

`rArr x^2-x*(1+i)-(1-i)*x+(1-i)*(1+i)=0`

Then the two roots belong to the following second degree equation:

`x^2-2*x+2=0`

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

The equation with roots 1 - i and 1 + i has to be determined. The simplest equation with these roots is (x - (1 - i))(x - (1+i)) = 0.

(x - (1 - i))(x - (1+i)) = 0

=> (x - 1 + i)(x - 1 - i) = 0

=> (x - 1)^2 - i^2 = 0

=> x^2 + 1 - 2x + 1 = 0

=> x^2 - 2x + 2 = 0

The simplest quadratic equation with the roots 1 + i and 1 - i is x^2 - 2x + 2 = 0 

atyourservice's profile pic

atyourservice | Student, Grade 11 | (Level 3) Valedictorian

Posted on

1 - i and 1 + i

the first step is to group these solutions:

(x - 1 + i ) (x - 1 - i )

the reason we have x there is because in order to solve the equation would have looked something like this x - 1 + i =0 in order to get the solutions.

now F.O.I.L this stands for First Outer Inner Last it refers as to how you will multiply these numbers:

 (x - 1 + i)(x - 1 - i) = 0

 (x - 1) + i(x - 1) - i 

 (x - 1)^2 - i^2 = 0

i^2 is the same as -1

(x - 1)^2 -(-1) = 0

(x - 1) (x - 1)

FOIL the parenthesis, you should end up with:

x^2 -x -x +1

combine like terms

x^2 -2x + 1

add in the other result

x^2 - 2x +1 + 1 = 0

x^2 - 2x + 2 = 0

We’ve answered 318,988 questions. We can answer yours, too.

Ask a question